Bronchial pulmonary carcinoma: molecular and clinical characterization: histology, mutations, staging, therapeutics and survival - Cabral, Sara Carla Moura (2015)
Trabalho final de mestrado integrado em Medicina, apresentado à Faculdade de Medicina da Universidade de Coimbra.